Lung Disease in Rheumatoid Arthritis (Respiratory Medicine,, 2018)
This book addresses the manifestation of lung disease in patients with rheumatoid arthritis (RA). Lung disease in RA is common and often associated with significant morbidity and mortality. This stems partially from the nature of RA and partially from the many therapies used to manage RA that are associated with pneumotoxicity. Despite the severity and commonality of this comorbidity, little has been written on the topic. This book thus takes a multidisciplinary approach to provide: a concise overview of RA and why lung disease so commonly coincides with it; overviews of the specific lung diseases, including interstitial lung disease, and their epidemiology, associated imaging, histopathology, biomarkers, and management; a presentation of risk factors for these diseases; and specifics on what still needs to be uncovered about these pulmonary manifestations. Lung Disease in Rheumatoid Arthritis is a comprehensive and practical resource for clinicians and clinician scientists in pulmonology, rheumatology, pathology, and primary care.